G489(P) A year in the life of the paediatric sexual assault service – providing a service for the local population. (25th October 2020) - Shonfeld, L; Straw, F
Abstract : Background: A medical examination may be considered in the Paediatric Sexual Assault Service when there is an allegation or suspicion of sexual abuse in a child or young person. It is important to ensure a universally equitable service for all young people, including those with disabilities. Services delivering this must be high quality, readily accessible, open access services for all regardless of gender or sexual orientation. Our local service has been operating for more than a year and aims to provide this high quality service. Aims: The aim of this project was to evaluate the data over a year to look at the age, sex/gender, ethnicity and address of each of the young people to ensure that the service is open to all, and to provide data to improve awareness and access to the service. Methods: We identified every child and young person who was examined in the service and collated data of their sex, ethnicity, age and any identified disabilities. Using post codes we mapped the use of the service across the region producing a pictorial representation of the use of the service. Results: There were 410 children and young people seen. 43 (10%) Male, 364 (89%) Female, 3 (1%) Transgender. The largest number of examinations were carried out for older children >13 although there was a spread of examinations across all ages 0–18. The largest ethnic group was White British (261) followed by White-Other (29) and Black or British Black African (10). 53 (12%) had a physical or learning disability. A map of the postcodes showed a spread across the region, with a predictable peak in each of the urban areas. Conclusion: The service provided care to children and young people of all ages and gender, across a wide spread of ethnicities and across the region. Females, teenagers and people from White British backgrounds made up the largest groups. There is still work to be done to reduce the stigma attached to an examination, to educate professionals about the holistic care provided and to ultimately improve access to the service for all.